MHD mixed convection in a lid-driven cavity with corner heater - Öztop, Hakan Fehmi; A-Salem, Khaled; Pop, Loan (Pergamon-Elsevier Science Ltd, 2011)
Laminar mixed convection flow in the presence of magnetic field in a top sided lid-driven cavity heated by a corner heater was considered. The corner heater is under isothermal boundary conditions with different length in bottom and right vertical walls. Finite volume technique was used to solve governing equations. The temperature of the lid is lower than that of heater. The study is performed for different Grashof and Hartmann numbers at Re = 100. The obtained results showed some very interesting results. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Magnetohydrodynamics; Lid-driven cavity; Corner heater